Phenomena 0f code switching and code mixing in teacher and student speaking in learning interactions in bashrah classes Al-Azhar Pare Course Institution - Wachida Muhlis (Aksara: Jurnal Bahasa dan Sastra, 2023)
This study aims to describe the phenomena of code switching and code mixing that occur in speech events of interactions between teachers and students in the Bashrah class. The Bashrah class is one of the class names at the Al-Azhar Arabic language course in Pare Kediri. The main problem in this study is the form of code switching and code mixing that occurs in the speech interaction between teachers and students in their learning. This research includes the type of qualitative descriptive research. The subject of this study is the speech phenomenon that occurs in the interaction of teachers and students in the Bashrah class at the Al-Azhar Pare Kediri course institution. The object of this research is speech that contains code-switching and code-mixing in teacher and student interactions in the Bashrah class. The data was obtained using participant observation, interviews techniques and field notes. Data analysis wascarried out by reducing data, then recording sentences that fall into the category of code switching and code mixing. The limitations in this study are time constraints that make this research less than optimal. The author hopes that this research can be useful for readers, and hopefully this research can be developed by others. Keywords: Phenomena, Code Switching, Code Mixing, Speech